Vaccination in the Time Of COVID-19: Survey Study at the University of Tlemcen in the Spring of 2022 - Ilyes Zatla; Lamia Boublenza; Soumia Zair; Nesrine Diab (Journal of Epidemiology and Public Health, 2023)
Background: The novel human coronavirus SARS-CoV-2 causing COVID-19 with symptoms ranging from the common cold to pneumonia, has been responsible for the current health crisis, it has spread rapidly at record speed leaving many deaths of different ages and different ethnicities, and in order to stop this propagation, scientists rushed to create several efficient vaccines against this virus, and despite being marketed in all countries of the world, opinions diverged between supporters and opponents. This prompted us to carry out this survey study on vaccination against COVID-19 at the University of Tlemcen, with the aim of exploring the perceptions and opinions of participants on vaccination and vaccines in general. Subjects dan Method: A cross-sectional study was conducted over a two months period, using a questionnaire to collect data from Teachers and Students of the University of Tlemcen with a 382 calculated sample size, the survey was shared via email and social media networks. Variables of interest included exposure to the pathogen, the laboratory testing results, effectiveness and adherence to the preventive measures, while also monitoring the vaccine acceptance and hesitancy. Descriptive and statistical analysis were run on SPSS Statistics with a p-value <0.050. Results: The majority of respondents for this study belonged to young people of the female gender (37.4%), despite the latter, men were the most vaccinated (53.4%), fortunately, most of them also acknowledge the association between prevention and vaccination (94.6%). Conclusion: Vaccine reluctance is a huge problem in the face of a pandemic that is not yet over. Even with the availability of vaccines and vaccination campaigns, unexplained fear due to rumors and conspiracy theories on social media still wins over the public about the safety of these vaccines. Keywords: COVID-19, SARS-CoV-2, investigation, vaccination, University of Tlemcen. Correspondence:Ilyes Zatla. Laboratory of Microbiology applied to the Food industry, Biomedical and the Environment, Faculty of Natural and Life Sciences, Earth and Universe Sciences. Department of Biology. University of Tlemcen, Algeria. E-mail: ilyes.zatla@univ-tlemcen.com. Mobile: +213540315422.